Dissolved oxygen concentration, trace elements concentration, carbon isotope composition and foraminifera assemblages data from Western Norwegian fjords - Mattia Ferraro; Bjørg Risebrobakken; Irina Polovodova Asteman; Elin Darelius; Amandine Tisserand; Natalya Gallo; Anne Gro Vea Salvanes (PANGAEA, 2025)
This dataset present benthic foraminiferal assemblage data, stable carbon isotopes and Mn/Ca, both measured on Hyalinea balthica (size fraction between 150 and 355 μm), from marine surface sediment samples (0-0.5 cm) from 9 sites located in western Norwegian fjords (more specifically, Fensfjorden, Masfjorden, Haugsværfjorden, Matrefjorden, Lurefjorden and Mangerfjorden). In addition, δ13CDIC and Mn/Ca measured at water samples from the same locations are presented together with corresponding oxygen data measured by CTD deployments. The analyses were done between 2022 and 2024 at Trace Element Lab at NORCE in Bergen on an Agilent 720 inductively coupled plasma optical emission spectrometer (ICP-OES), at the ICP-MS Laboratory in the Department of Earth Sciences at the University of Bergen, at FARLAB at the University of Bergen (MAT253 mass spectrometer and a Thermo Scientific Gasbench connected to a Thermo Scientific Delta V+ isotope ratio mass spectrometer). Apparent Oxygen Utilisation rate (AOU) is calculated, using the gsw_O2sol toolkit for python to calculate the difference between the O2 gas solubility and measured O2. The data presented was collected to investigate the potential of benthic foraminiferal based and geochemical (δ13C and Mn/Ca) proxies to reflect dissolved oxygen levels in coastal fjord settings. All sediment samples were collected using a Multi Corer onboard R/V Kristine Bonnevie, in February 2022. Water samples were also collected from Niskin bottles on the CTD (Conductivity, Temperature, and Depth) rosette during the same R/V Kristine Bonnevie February 2022 cruise and from cruises to Lurefjorden, Haugsværfjorden, Sørfjorden, and Osterfjorden in 2021, 2022 and 2023.